2017
DOI: 10.1016/j.cherd.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic performance of a pulsed extraction column containing ZnO nanoparticles: Drop size and size distribution

Abstract: Highlights:  Mean drop size and size distribution is determined in a horizontal extraction column in presence of ZnO nanoparticles.  Presence of nanoparticles reduces the interfacial tension and consequently drop sizes.  Density of small droplets considerably increases at the first concentration of adding nanoparticles.  The maximum entropy principle is considered for the determination of the drop size distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The maximum entropy approach is another method which is recently developed in order to evaluate the droplet size distribution in extraction columns [77]. It was found that the maximum entropy method has better ability to predict the experimental data.…”
Section: Hydrodynamic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum entropy approach is another method which is recently developed in order to evaluate the droplet size distribution in extraction columns [77]. It was found that the maximum entropy method has better ability to predict the experimental data.…”
Section: Hydrodynamic Characteristicsmentioning
confidence: 99%
“…The authors proposed a new correlation for the prediction of mean drop size in terms of the operational parameters, physical properties, and nanoparticle concentration. Furthermore, the maximum entropy principle was found to be an appropriate method for modeling the drop size distribution in pulsed plate columns [77].…”
Section: Effect Of Nanoparticles On Droplets Behaviormentioning
confidence: 99%
“…In the liquid-liquid extraction step, extraction columns with high removal capability for sulfurcontaining compounds should be applied. Various extraction columns, including a rotating disk contactor (Torab-Mostaedi et al, 2017;Asadollahzadeh et al, 2016), Kuhni column (Hemmati et al, 2015;Arab et al, 2017;Oliveira et al, 2008), packed column (Rahbar-Kelishami and Bahmanyar, 2012;Torab-Mostaedi and Safdari, 2009), pulsed column (Amani et al, 2017;Khooshechin et al, 2013;Usman et al, 2009), tray column (Sincuba et al, 2017), and spray column (Salimi-Khorshidi et al, 2013), are available. Single drop tests can provide valuable insights regarding the hydrodynamics of the complex systems in the liquidliquid extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Drop size and dispersed phase holdup together, determine the interfacial tension required for mass transfer . Therefore, it is important to be able to anticipate the mean drop size as a function of the column geometry, operating parameters and the physical properties of liquid–liquid systems in order to design and analyze the performance of Scheibel extraction column.…”
Section: Introductionmentioning
confidence: 99%